2009
DOI: 10.1007/s11256-008-0117-7
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Certified Teachers in Urban Small Schools: Where Policy Reform Meets the Road

Abstract: In this study we explore the experiences of new teachers in urban schools at the intersection of three major policy agendas-alternative certification, new teacher retention, and the small schools movement. We examine alternatively certified teachers' perceptions of the rewards and challenges of teaching in small schools, the support neophyte teachers seek and receive in these unique educational settings, and the reality of small school implementation in a modern urban environment. The findings have implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The importance of support and mentoring for all early career teachers was also emphasised in the literature on career-change teachers (Allen, 2007;Carter & Keiler, 2009;Chambers, 2002;Grier & Johnston, 2009;Kelley, 2004;Kember, 2008). Feistritzer and Chester (2003) concurred with the comments on the need for mentoring for alternatively qualified teachers.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The importance of support and mentoring for all early career teachers was also emphasised in the literature on career-change teachers (Allen, 2007;Carter & Keiler, 2009;Chambers, 2002;Grier & Johnston, 2009;Kelley, 2004;Kember, 2008). Feistritzer and Chester (2003) concurred with the comments on the need for mentoring for alternatively qualified teachers.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The aggregate impact of program elements upon beginning teachers' workload also contributed to the negative perceptions of program elements. Carter and Keiler (2009) noted, "part of the teachers' responsibility became managing both the interactions with the multiple mentors and the time this required" (p. 450). On the contrary, another study found the naturally increased workload of a new teacher meant that they were spending more time at work and therefore, more time in an environment where they can ask questions to colleagues (Nasser-Abu Alhija & Fresko, 2010).…”
Section: Structure Of Induction and Mentoring Programsmentioning
confidence: 99%
“…In contrast to positive impacts described in studies where teachers received supports from school administrators, a number of the studies indicated negative outcomes of principals' perceived lack of involvement or provision of support. For example, researchers noted ECTs rarely found curriculum support from their administrators as departments rarely had an administrator in their own field (Carter & Keiler, 2009). Similarly, Morris and Morris (2013) discussed overall perceptions of principals' lack of communication, lack of assistance in improving student behaviour, and lack of sufficient resources in support of beginning teachers.…”
Section: Impact and Outcomementioning
confidence: 99%
“…This has been particularly important for urban school districts such as those that have been reported to have graduation rates below 40%, including Detroit (21.7%), Baltimore (38.5%) and New York City (38.9%) (Toppo 2006). In addition to documented low graduation rates, low levels of academic achievement and poor student attendance (Neild and Balfanz 2006), as well as high teacher turnover (Carter and Keiler 2009) characterize such urban school districts. These schools tend to serve students who receive free and reduced-price lunch, as well as a preponderance of students from minority groups (Neild and Balfanz 2006).…”
Section: Literature Reviewmentioning
confidence: 99%